Pembuatan Aplikasi Layanan Pengguna Perpustakaan Universitas Kristen Petra Dengan Fitur Barcode Dan Metode REST Pada Pengusulan Koleksi - Septian Jati Winayaka; Justinus Andjarwirawan; Lily Puspa Dewi (Jurnal Infra, 2017)
The making of the application user services library of Petra Christian University with barcode features and methods REST on proposing a collection of processes existing library services in Petra Christian UniversityVarious processes of library services that exist in Petra Christian University currently has been running pretty well. But the times made Petra Christian University Library should always innovate in his Ministry. Starting from the previous manual system revamp to become ter-computerized, providing access to information that is complete and can be accessed from a variety of technologies. Application user services library of Petra Christian University is designed for users in accessing memepermudah various services there is Petra Christian University Library, such as providing information about the collection that is being borrowed, and information about the collections who want ordered. In addition the application also provides a feature proposing the collection, so that users can suggest various collections such as books, journals, magazines and so on to the librarian to add to an existing collection at the library. The results of the application shows that this app can help users find out various information about the collections which are being borrowed and booked. The application can also simplify the user in doing the booking service collection. Then the existence of the proposals feature helps make it easier to propose a collection of users. In addition a Web service that is created can facilitate data exchange between the applications with the server and can be developed for the application of the existing library.